S1417CD: A Prospective Multicenter Cooperative Group-Led Study of Financial Hardship in Metastatic Colorectal Cancer Patients. (4th January 2022) - Shankaran, Veena; Unger, Joseph M; Darke, Amy K; Suga, Jennifer Marie; Wade, James L; Kourlas, Peter J; Chandana, Sreenivasa R; O'Rourke, Mark A; Satti, Suma; Liggett, Diane; Hershman, Dawn L; Ramsey, Scott D
Abstract: Background: Financial toxicity is a growing problem in oncology, but no prior studies have prospectively measured the financial impact of cancer treatment in a diverse national cohort of newly diagnosed cancer patients. S1417CD was the first cooperative group-led multicenter prospective cohort study to evaluate financial hardship in metastatic colorectal cancer (mCRC) patients. Methods: Patients aged 18 years or older within 120 days of mCRC diagnosis completed quarterly questionnaires for 12 months. We estimated the cumulative incidence of major financial hardship (MFH), defined as 1 or more of increased debt, new loans from family and/or friends, selling or refinancing home, or 20% or more income decline. We evaluated the association between patient characteristics and MFH using multivariate cox regression and the association between MFH and quality of life using linear regression. Results: A total of 380 patients (median age = 59.9 years) were enrolled; 77.7% were White, 98.0% insured, and 56.5% had annual income of $50 000 or less. Cumulative incidence of MFH at 12 months was 71.3% (95% confidence interval = 65.7% to 76.1%). Age, race, marital status, and income (split at $50 000 per year) were not statistically significantly associated with MFH. However, income less than $100 000 and total assets less than $100 000 were both associated with greater MFH. MFH at 3 months was associated with decreased social functioning and quality of life at 6 months. Conclusions: Nearly 3 out of 4 mCRC patients experienced MFH despite access to health insurance. These findings underscore the need for clinic and policy solutions that protect cancer patients from financial harm.